Iron(ii) coordination polymer catalysed hydroboration of ketones. Issue 29 (5th July 2018) - Li, Li; Liu, E; Cheng, Jessica; Zhang, Guoqi
Abstract : Catalytic hydroboration of ketones with pinacolborane was achieved using a two-dimensional iron(ii ) coordination polymer based on a divergent 4, 2′;6′, 4′′-terpyridine ligand. Abstract : Catalytic hydroboration of ketones with pinacolborane was achieved with a 2D iron(ii ) coordination polymer (CP) of a divergent 4, 2′;6′, 4′′-terpyridine (tpy) derivative under mild conditions with high efficiency. This solid iron catalyst system is more active towards the hydroboration of ketones than that of aldehydes, displaying a different trend of reactivity from known homogeneous iron hydroboration catalysts.